(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: The Task-Based Approach (TBA) has emerged as a significant methodology in language teaching, emphasizing meaningful communication and the completion of real-life tasks as the central focus of learning. This approach differs from traditional methods that prioritize grammar instruction and language drills. Instead, TBA fosters a learner-centered environment where language is used as a tool for achieving specific goals. This article explores the principles and stages of the Task-Based Approach, its advantages and challenges, and its effectiveness in modern language teaching. By emphasizing communication and authentic learning experiences, TBA is a vital tool in the development of language learners’ fluency, critical thinking, and problem-solving abilities.